2022
DOI: 10.1530/eje-22-0530
|View full text |Cite
|
Sign up to set email alerts
|

Fat, adipokines, bone structure and bone regulatory factors associations in obesity

Abstract: Context: Obese adults (OB; BMI ≥30) have higher bone mineral density (BMD) and more favourable bone microarchitecture than normal weight adults (NW; BMI 18.5-24.9). Objective: To identify which fat compartments have the strongest association with bone density and bone turnover and whether biochemical factors (adipokines, hormones and bone regulators) are likely to be important mediators of the effect of obesity on bone. Design: Cross-sectional, observational, matched case-control study. Setting: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Our systematic search identified 42 cross-sectional studies ( 12 , 13 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 , 83 , 84 , 85 ) and two cohort investigations ( 60 , 78 ) (with 33,815 participants) that investigated the potential relationship between 25(OH)D serum concentrations and anthropometric/adiposity indices in adults and/or elderly population. The studies about the link between 25(OH)D serum level and anthropometric indices in adults and/or elderly population were carried out in the following countries: 9 studies from USA, 3 from UK, 3 from Spain, 2 from Turkey, 4 from Saudi Arabia, 2 from Iran, 2 from India, 2 from Italy, 2 from Germany, and 18 others from China, UAE, Pakistan, Australia, Finland, England, Portugal, Malaysia, Bulgaria, Austria, Canada, Denmark, Greece, New Zealand, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our systematic search identified 42 cross-sectional studies ( 12 , 13 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 , 83 , 84 , 85 ) and two cohort investigations ( 60 , 78 ) (with 33,815 participants) that investigated the potential relationship between 25(OH)D serum concentrations and anthropometric/adiposity indices in adults and/or elderly population. The studies about the link between 25(OH)D serum level and anthropometric indices in adults and/or elderly population were carried out in the following countries: 9 studies from USA, 3 from UK, 3 from Spain, 2 from Turkey, 4 from Saudi Arabia, 2 from Iran, 2 from India, 2 from Italy, 2 from Germany, and 18 others from China, UAE, Pakistan, Australia, Finland, England, Portugal, Malaysia, Bulgaria, Austria, Canada, Denmark, Greece, New Zealand, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…The age of participants was >18 years old. Among the included studies, 27 articles ( 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 84 , 85 ) involved both sexes, and 17 investigations conducted in females ( 12 , 13 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ) and males ( 69 , 70 , 71 ) only. The included studies mostly considered the following potential confounders: age, sex, season of blood sampling, smoking, vitamin D status, body fat mess, weight, height, BMI, IGF-1, PTH, UVB, alcohol, tobacco, sports, use of multivitamin supplements, menopausal status/HRT use, physical activity, socioeconomic status, income, job, obesity, education level, lifestyle, sun exposure, lean mass, nutrient intake, residence type, race, ethnicity, serum calcium, magnesium and phosphate, GFR, 25(OH)D, CRP, WC, month of blood collection, marital status, district, area, latitude, phosphorus, serum alanine aminotransferase, creatinine, and IL-6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T2DM is associated with obesity, which raises the issue of skeletal frailty in T2DM due to obesity factors. T Vilaca et al reported that obesity-promoted bone mass accumulation was associated with enhanced bone mechanical loading and cytokine or hormone secretion [ 62 ], consistent with patients with T2DM exhibiting normal or high BMD but did not reduce their fracture risk [ 12 ]. At present, weight loss is still one of the nutritional treatment goals for overweight/obese T2DM patients to improve glycemic control and reduce the risk of cardiovascular morbidity [ 57 ].…”
Section: Macronutrients and Micronutrientsmentioning
confidence: 99%